Comparison of the new RIDA qLine Allergy multiparameter immunoblot and the ImmunoCAP Specific IgE test for the identification of clinically relevant food and aeroallergen allergies - Hahn, Katharina K.; Schuppe, Marie C.; Hollstein, Moritz M.; Forkel, Susann; Buhl, Timo (Frontiers in Allergy, 2025)
BackgroundMultiparameter immunoblot testing is increasingly used as an alternative to multiple individual IgE analyses for type 1 allergies. This study investigated the performance of an inexpensive immunoblot method, the RIDA qLine allergy test system (R-Biopharm AG), vs. the current gold standard.MethodsThree study-specific panels with 57 individual allergens (food and aeroallergens) were analyzed in serum samples from 200 patients with signs and symptoms of IgE-mediated allergies, using both the RIDA qLine Allergy and the reference method, the ImmunoCAP Specific IgE test (Thermo Fisher Scientific). In case of divergent results, corresponding allergens were remeasured using the secondary reference method, the 3gAllergy Specific IgE Universal Kit (Siemens). The clinical diagnoses of the 200 patients were included. In addition, a cross-reactive carbohydrate determinant (CCD)-inhibitor was used in the testing to decrease the incidence of positive CCD bands.ResultsThe mean overall agreement of all food and aeroallergens with the reference methods was 94.9%. Qualitative evaluation showed an average negative percent agreement of 98.9% and an average positive percent agreement of 75.1% for all individual allergens after testing with both reference methods. The additional treatment of samples with the CCD inhibitor successfully reduced the occurrence of positive CCD reactivity after retesting.ConclusionThe comparative analysis of RIDA qLine Allergy with the reference methods for specific IgE detection revealed a strong correlation between serum IgE levels measured across these platforms and clinical presentations, while also highlighting the necessity for careful contextual interpretation of results. Standardized allergen extracts would improve independent comparisons of different allergy testing methods.